Ответы и объяснения

2013-12-05T21:15:45+04:00
I вариант:
№1
а) sin(π / 6)*sin(π / 4)*sin(π / 3)*sin0= 0
б) 2sin(π / 2)-3cos(π)+sin(3π/2)= 2+3-1=4
в) ctg(π / 4)* cos(π/6)*tg(π / 3)=cos(π/6)=0,86602540378≈0,9
г) извини, бро :(

№2
а) (1-сosα)(1+cosα)=1-cos²α=sin²α
б) \frac{1-sin ^{2} \alpha  }{cos ^{2} \alpha  } = \frac{cos ^{2} \alpha }{cos ^{2} \alpha } =1
в) cos²α+(1-sin²α)=  cos²α+ cos²α= 2cos²α
г)  \frac{1-cos ^{2} \alpha  }{1-sin^{2} \alpha} =  \frac{sin^{2} \alpha}{cos ^{2} \alpha  }
д) sinα*cosα*tgα sorry:(
е)  \frac{sin2 \alpha }{2cos \alpha } = \frac{2sin \alpha cos \alpha }{2cos \alpha } =sin \alpha
 

II вариант:
№1
а) ..=0
б) ..=-4
в,г-?
№2
а)..=1-sin ^{2}  \alpha =cos ^{2}  \alpha
б) ..=1
в)..=2sin ^{2}  \alpha
г)..=  \frac{cos ^{2} \alpha  }{sin ^{2}  \alpha }
д) &
e) ..= \frac{2sin \alpha cos \alpha    }{2sin \alpha} = cos \alpha